Estrategias tendientes a mejorar la rentabilidad, con enfoque medioambiental en las empresas del sector transporte del Municipio De Duitama - Becerra Vasquez, Erika Yurany; Giraldo Valencia, Liseth Andrea (Universidad Antonio Nariño, 2023)
The purpose of this study is to make known that sustainable development in transport companies implies that various practices and policies are carried out that seek to minimize the environmental and social impact of their operations, while guaranteeing their economic viability. In the long term, which will help reduce costs and expenses due to the unreasonable use of resources, knowledge of this practice will serve each of the entrepreneurs to be clear about the advantages that can be obtained under a series of conditions for their proper driving. We will contemplate the idea and we will give different recommendations with which the transport companies, specifically the Transct SAS company, with which we are basing ourselves mainly to carry out our study, can become a friendly company with the environment, and achieving a sustainable development that It can also lead to improve the profitability of the company due to the benefits that this development provides. We will present different methods and standards that can benefit the company, achieving sustainable development. There will be talk about standards such as ISO or regulations that can be implemented and help improve efficiency and effectiveness in the processes that are carried out daily in the company, to have benefits in the tax field, in order to have an improvement in profitability.